If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(0.2 + 0.3x) = 1 (0.2 * x + 0.3x * x) = 1 (0.2x + 0.3x2) = 1 Solving 0.2x + 0.3x2 = 1 Solving for variable 'x'. Reorder the terms: -1 + 0.2x + 0.3x2 = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 0.2x + 0.3x2 = 0 Begin completing the square. Divide all terms by 0.3 the coefficient of the squared term: Divide each side by '0.3'. -3.333333333 + 0.6666666667x + x2 = 0 Move the constant term to the right: Add '3.333333333' to each side of the equation. -3.333333333 + 0.6666666667x + 3.333333333 + x2 = 0 + 3.333333333 Reorder the terms: -3.333333333 + 3.333333333 + 0.6666666667x + x2 = 0 + 3.333333333 Combine like terms: -3.333333333 + 3.333333333 = 0.000000000 0.000000000 + 0.6666666667x + x2 = 0 + 3.333333333 0.6666666667x + x2 = 0 + 3.333333333 Combine like terms: 0 + 3.333333333 = 3.333333333 0.6666666667x + x2 = 3.333333333 The x term is 0.6666666667x. Take half its coefficient (0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. 0.6666666667x + 0.1111111112 + x2 = 3.333333333 + 0.1111111112 Reorder the terms: 0.1111111112 + 0.6666666667x + x2 = 3.333333333 + 0.1111111112 Combine like terms: 3.333333333 + 0.1111111112 = 3.4444444442 0.1111111112 + 0.6666666667x + x2 = 3.4444444442 Factor a perfect square on the left side: (x + 0.3333333334)(x + 0.3333333334) = 3.4444444442 Calculate the square root of the right side: 1.855921454 Break this problem into two subproblems by setting (x + 0.3333333334) equal to 1.855921454 and -1.855921454.Subproblem 1
x + 0.3333333334 = 1.855921454 Simplifying x + 0.3333333334 = 1.855921454 Reorder the terms: 0.3333333334 + x = 1.855921454 Solving 0.3333333334 + x = 1.855921454 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.3333333334' to each side of the equation. 0.3333333334 + -0.3333333334 + x = 1.855921454 + -0.3333333334 Combine like terms: 0.3333333334 + -0.3333333334 = 0.0000000000 0.0000000000 + x = 1.855921454 + -0.3333333334 x = 1.855921454 + -0.3333333334 Combine like terms: 1.855921454 + -0.3333333334 = 1.5225881206 x = 1.5225881206 Simplifying x = 1.5225881206Subproblem 2
x + 0.3333333334 = -1.855921454 Simplifying x + 0.3333333334 = -1.855921454 Reorder the terms: 0.3333333334 + x = -1.855921454 Solving 0.3333333334 + x = -1.855921454 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.3333333334' to each side of the equation. 0.3333333334 + -0.3333333334 + x = -1.855921454 + -0.3333333334 Combine like terms: 0.3333333334 + -0.3333333334 = 0.0000000000 0.0000000000 + x = -1.855921454 + -0.3333333334 x = -1.855921454 + -0.3333333334 Combine like terms: -1.855921454 + -0.3333333334 = -2.1892547874 x = -2.1892547874 Simplifying x = -2.1892547874Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.5225881206, -2.1892547874}
| -(7x+9y+5)= | | (2x^2)-5x=33 | | sinx=-0.4x+1.2 | | (2x^2)-(5x)=33 | | 9*10x=17 | | y^2+2y+4=5ty^2 | | 2x+12y=-22 | | 2(3)-6=-3y | | ln(x)=56 | | 1.5y-x=-6 | | -18+9r-6r+4= | | 0=x^5+5x^4-2x^3-24x^2 | | y=4x^2+10x-4 | | 36+5t=-12-3t | | 5n-8=4n+2n | | g(c+1)=x+4 | | 2(x+3)+3x=-3(x-2)+8x | | 9.2x-18.4=8.9x-53.4 | | f(x)=6x^2+78 | | -72x=20x+92 | | 26=-68x+42x | | 6v^2-11v-35=0 | | 3a-4b+c-d=0 | | ln(x+6)+ln(x+5)=ln(5) | | f(x)=2x^4-x^3+49x^2-25x-25 | | n-1.4n-1=6(n-2.3) | | C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 |